2021
DOI: 10.1038/s41598-021-97723-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and longitudinal trend of traumatic cataract wound dehiscence in patients with blunt ocular injury

Abstract: Longitudinal trends on traumatic cataract wound dehiscence are scant. In this study, we present the characteristics of traumatic cataract wound dehiscence using 15 years of longitudinal trend in one of the largest medical centers in Taiwan for a period when cataract surgeries were gradually shifting from extracapsular cataract extraction (ECCE) to phacoemulsification. All patients with a prior cataract surgery who suffered from blunt open globe trauma between 2001 and 2015 at a tertiary referral center in Taiw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…To better understand visual recovery after surgery or trauma, many researchers have investigated the relationship between macular [3][4] , retinal [5][6] , and vireteal [7] injuries caused by diseases or trauma. Hou et al [8] found that macular injury involving the fovea or a thin optic nerve fiber layer results in severe vision loss. Phillips et al [9] found that in the lens and anterior chamber, timely treatment and effective control can effectively help the recovery of VA. Liang et al [10] found that postoperative VA was positively correlated with cube volume and cube average thickness (CAT).…”
Section: Introductionmentioning
confidence: 99%
“…To better understand visual recovery after surgery or trauma, many researchers have investigated the relationship between macular [3][4] , retinal [5][6] , and vireteal [7] injuries caused by diseases or trauma. Hou et al [8] found that macular injury involving the fovea or a thin optic nerve fiber layer results in severe vision loss. Phillips et al [9] found that in the lens and anterior chamber, timely treatment and effective control can effectively help the recovery of VA. Liang et al [10] found that postoperative VA was positively correlated with cube volume and cube average thickness (CAT).…”
Section: Introductionmentioning
confidence: 99%
“…4 Second, diagnosis of TCs can be challenging because of media opacity secondary to an opaque cornea and the presence of hyphema or severe fibrinous reaction. 5 Although cataract extraction and intraocular lens (IOL) implantation are usually required and reasonable, the timing of the operation and best surgical approach is controversial. 6,7 Furthermore, the management of complications related to TCs, such as intraocular inflammation and zonular weakness, is critical.…”
mentioning
confidence: 99%